Trophic Path of Marked Exuviae Within Colonies of Coptotermes gestroi (Blattodea: Rhinotermitidae). Issue 2 (14th March 2023) - Tong, Reina L; Choi, Eun-Kyung; Ugarelli, Kelly; Chouvenc, Thomas; Su, Nan-Yao
Abstract: Nitrogen, a limiting growth factor in wood-feeding insects, was hypothesized to play a role in the recently discovered behavior of subterranean termites returning to the nest to molt. Coptotermes gestroi (Wasmann) exuviae is approximately 11% N by dry weight, and therefore a potentially rich source of recyclable nitrogen. Exuviae from a C. gestroi colony were marked with immunoglobulin G (IgG) and were fed to two-year-old C. gestroi colonies. IgG-marked exuviae were detected with an enzyme-linked immunosorbent assay. The IgG marker was later detected in every caste and life stage except first-instar larvae (L1 ). The proportion of individuals positive for the marker varied by caste, with the queens always being positive for the marker. The queens and second-or-higher-instar workers (W2+ ) had significantly higher concentrations of the marker than the eggs and L1 . The trophic path of exuviae includes individuals that directly fed on marked exuviae (workers and possibly second-instar larvae) and individuals that secondarily received marked exuviae through trophallaxis (queens, kings, and soldiers). This study described the trophic path of consumed exuviae and demonstrated its role in the recycling of nitrogen in a subterranean termite. Molting at the central nest may be an efficient means to transfer nitrogen from shed exuviae to recipients and may be a nitrogen recycling behavior conserved from a termite ancestor.